The seismic signal and its meaning - Rosa, André Luiz Romanelli (Society of Exploration Geophysicists, 2018)
Filling the gap between theoretical literature and the routine activities of geophysicists in the oil industry, The Seismic Signal and Its Meaning is a translation of the second edition of Análise do Sinal Sísmico, published in Portuguese by Sociedade Brasileira de Geofísica (SBGf). For those performing acquisition, processing, and/or interpretation, this book will aid an understanding of how practical problems may have important links to seismic data analysis theory. With an emphasis on providing an objective description of the physical and mathematical aspects that support these links, the rules necessary for robust reservoir characterization are presented. With an extensive development of Gassmann's (and Biot) theory and its relevance, the book concentrates on phase and amplitude distortions to the seismic signal, the physical processes that it undergoes, and the interpretation methods to recover rock physics properties. Capturing 30 years of teaching and improvement as a part of Petrobras internal courses, the book is a modern treatment, reflecting the many advances that have occurred in geophysics. The book serves as both a text and a reference.
Translation of the second edition of: Análise do sinal sísmico.
Keywords: Seismic prospecting.; Seismic waves.; Signal processing.; elektronické knihy; electronic books